Study on different sintering temperature on the composite ferum and cobalt reinforced with silicon carbide - Durairaj Ehambron (Universiti Malaysia Perlis, 2008)
Particulate-reinforced metal matrix composites (MMCs) have become more attractive to researches because of the problem of anisotropy and high cost of fibre reinforced MMCs. This study involves the fabrication of MMCs with different sintering temperature. The composite mixed with different weight percentage which 69 wt% of Fe, 11 wt% of Co and 20 wt% of SiC with roll mill machine under speed 150 rpm around 2 hour. Compaction processes continue with pressure 250 MPa around 2 minute. Samples were sintered for 2 hours with different sintering temperatures which are 700°C, 800°C, 900°C and 1000°C. Testing were conducted on the samples to know the physical and mechanical properties. Reinforcement particles distribution can observe by scanning electron microscope. Porosity, density, hardness test and shrinkage were measured to know the optimum properties of the samples. As a result, 700°C is optimum sintering temperature compare then other sintering temperature. Its because sample at 700°C have low value of porosity percentage which is 20.7% compare with the other sintering temperature. At this sintering temperature, the pores at microstructure are very rare when observe by SEM resulting the highest density value which is 4.6031 g/cm³. These statements give chance for highest value of hardness which is 148.98 HV. When the sintering temperature increases, the pores on microstructure also increase which cause to increment of porosity value. Besides that, when the sintering temperature was increase, the density value start to decrease. And the same thing also happens to hardness value which reduced sharply. So, from overall 700°C is optimum sintering temperature which gives best physical and mechanical properties for this research.